Correlation Among Education, Knowledge, And Economics Of Mother Toward Antipyretic Drug Usage For Toddler In Kangkung Village OKUT Sumsel 2017 - Rennie Puspa Novita; Atika Akbari; Nikita Surya Dharma; Endang Putria Sukma (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2018)
Fever is a symptom mostly happen with all diseases which condition shows elevated body temperature above normal (38°C) that are common among toddler. Handling fever using antipyretics should be considered related to the rationale of its use. Rationality aspect which include indication accuracy, precision of medicine, patient accuracy, dosage accuracy and precision of administration, and as well as alert to side effects. Handling fever in toddlers is very dependent on the role of parents especially mother. Different maternal education, knowledge, and economics will result in the rationale of the use of different antipyretic drugs. This study aimed to investigate whether there is relation among education, knowledge, and economics of mother toward antipyretic drug usage for toddler in Kangkung Village OKUT SUMSEL 2017 by using cross sectional design. The sample was collected using simple random sampling to get 47 samples which fulfilled the inclusion criteria. The data were collected by interview based on questionnaire and analyzed by Chi-Square test using SPSS® version 23.0. The data presented descriptively showed most of the respondents were highly educated (66%), high knowledge (61.7%), and low economic level (93.6%) and the rational use of antipyretic for toddler were 100% for appropriate drug indication, precision of medicine, patient appropriateness, and alert for side effects, as well as 31.9% dosage precision and mode of administration. The result of Chi-Square test showed that the p value for education level (p >0.05) and economic level (p >0.05) had no significant correlation, meanwhile the knowledge level (p <0.05) showed significant different to the rational use of antipyretic for toddler. It can be concluded that the knowledge toward of mother affect the rational use of antipyretic for toddler in Kangkung village OKUT regency SUMSEL 2017.